Novel Small Molecule Inhibitors of Protein Kinase D Suppress NF-kappaB Activation and Attenuate the Severity of Rat Cerulein Pancreatitis - Yuan, Jingzhen; Tan, Tanya; Geng, Meng; Tan, Grace; Chheda, Chintan; Pandol, Stephen J. (Frontiers in Physiology, 2017)
Nuclear factor-kappa B (NF-κB) activation is a key early signal regulating inflammatory and cell death responses in acute pancreatitis. Our previous in vitro studies with molecular approaches on AR42J cell showed that protein kinase D (PKD/PKD1) activation was required in NF-κB activation induced by cholecystokinin 8 (CCK) or carbachol (CCh) in pancreatic acinar cells. Recently developed small molecule PKD inhibitors, CID755673 and CRT0066101, provide potentially important pharmacological approaches to further investigate the effect of PKD in pancreatitis therapy. The aim of this study was to explore whether CID755673 and CRT0066101 block NF-κB activation with in vitro and in vivo models of experimental pancreatitis and whether the small molecule PKD inhibitors have therapeutic effects when given before or after the initiation of experimental pancreatitis. Freshly prepared pancreatic acini were incubated with CID755673 or CRT006101, followed by hyperstimulation with CCK or CCh. For in vivo experimental pancreatitis, rats were treated with intraperitoneal injection of CID755673 or CRT0066101 prior to or after administering cerulein or saline. PKD activation and NF-κB-DNA binding activity in nuclear extracts from pancreatic acini and tissue were measured. The effects of PKD inhibitors on pancreatitis responses were evaluated. Our results showed that both CID755673 or CRT0066101 selectively and specifically inhibited PKD without effects on related protein kinase Cs. Inhibition of PKD resulted in significantly attenuation of NF-κB activation in both in vitro and in vivo models of experimental pancreatitis. NF-κB inhibition by CID755673 was associated with decreased inflammatory responses and attenuated severity of the disease, which were indicated by less inflammatory cell infiltration, reduced pancreatic interleukin-6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1), decreased intrapancreatic trypsin activation, and alleviation in pancreatic necrosis, edema and vacuolization. Furthermore, PKD inhibitor CID755673, given after the initiation of pancreatitis in experimental rat model, significantly attenuated the severity of acute pancreatitis. Therapies for acute pancreatitis are limited. Our results indicate that small chemical PKD inhibitors have significant potential as therapeutic interventions by suppressing NF-κB activation.